Kepemimpinan dalam Mencegah Perpecahan Umat: Telaah Hadis Tentang Pentingnya Pemimpin Pemersatu Umat dan Bangsa: Leadership in Preventing Divisions in the Ummah: Study of the Hadith on the Importance of Unifying LeadersPeople and Nation - Chamdar Nur; Erwin Hafid; Abdurahman Sakka (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2025)
Leadership in Islam plays a crucial role in maintaining the unity of the Muslim ummah. This study examines the concept of ideal leadership according to the hadith of Prophet Muhammad SAW, particularly regarding the leader's role as a unifier of the ummah. The aim of this research is to identify the characteristics of a leader who can prevent division among the ummah and explore the relevance of Islamic teachings in addressing the challenges of social and political fragmentation in Indonesia. The methodology used is a literature review with a qualitative approach, analyzing relevant Qur'anic verses, hadiths on leadership, and supporting literature from tafsir scholars. The findings indicate that ideal leadership in Islam should be based on justice, obedience to Allah, and the ability to maintain the unity of the ummah. A wise leader will be able to mitigate conflicts and ensure the stability of the community. The relevance of hadith teachings on leadership is significant in facing the challenges of division within the ummah in Indonesia, in terms of social, political, and religious aspects. This study contributes to a deeper understanding of the role of leadership in preserving the unity of the Muslim ummah in the face of contemporary challenges and offers perspectives that can be applied in the current Indonesian context.